Water Street - Giff, Patricia Reilly 1935- (Lamb Books, 2006)
In the shadow of the construction of the Brooklyn Bridge, eighth-graders and new neighbors Bird Mallon and Thomas Neary make some decisions about what they want to do with their lives.